Long‐term, but not short‐term high‐fat diet induces fiber composition changes and impaired contractile force in mouse fast‐twitch skeletal muscle. Issue 7 (13th April 2017) - Eshima, Hiroaki; Tamura, Yoshifumi; Kakehi, Saori; Kurebayashi, Nagomi; Murayama, Takashi; Nakamura, Kyoko; Kakigi, Ryo; Okada, Takao; Sakurai, Takashi; Kawamori, Ryuzo; Watada, Hirotaka
Abstract: In this study, we investigated the effects of a short‐term and long‐term high‐fat diet (HFD) on morphological and functional features of fast‐twitch skeletal muscle. Male C57BL/6J mice were fed a HFD (60% fat) for 4 weeks (4‐week HFD) or 12 weeks (12‐week HFD). Subsequently, the fast‐twitch extensor digitorum longus muscle was isolated, and the composition of muscle fiber type, expression levels of proteins involved in muscle contraction, and force production on electrical stimulation were analyzed. The 12‐week HFD, but not the 4‐week HFD, resulted in a decreased muscle tetanic force on 100 Hz stimulation compared with control (5.1 ± 1.4 N/g in the 12‐week HFD vs. 7.5 ± 1.7 N/g in the control group; P  <   0.05), whereas muscle weight and cross‐sectional area were not altered after both HFD protocols. Morphological analysis indicated that the percentage of type IIx myosin heavy chain fibers, mitochondrial oxidative enzyme activity, and intramyocellular lipid levels increased in the 12‐week HFD group, but not in the 4‐week HFD group, compared with controls ( P  <   0.05). No changes in the expression levels of calcium handling‐related proteins and myofibrillar proteins (myosin heavy chain and actin) were detected in the HFD models, whereas fast‐troponin T‐protein expression was decreased in the 12‐week HFD group, but not in the 4‐week HFD group ( P  <   0.05). These findings indicate that a long‐term HFD, but not a short‐term HFD, impairs contractile force in fast‐twitch muscle fibers. Given that skeletal muscle strength largely depends on muscle fiber type, the impaired muscle contractile force by a HFD might result from morphological changes of fiber type composition. Abstract : Our findings indicate that a long‐term HFD, but not a short‐term HFD, impairs contractile force in fast‐twitch muscle fibers. The impaired muscle contractile force by a HFD might result from morphological changes of fiber type composition.